Development and application of a dry form of a new biopreparation for remediation of oil-contaminated soils in extreme continental climate conditions - Narmanova, R.; Appazov, N.; Puntus, I.F.; Niyazova, D.; Kuzhamberdieva, S.; Kanzhar, S.; Alimkhan, B.; Alzhanova, G. (Edelweiss Applied Science and Technology, 2025)
The article presents the results of research on the development of a dry form of the new biopreparation, the technology of production, and application for the reclamation of oil-contaminated soils in the extreme continental arid climate. A previously patented association of active crude oil degrader strains was used to develop the biopreparation (Pseudomonas putida KZ3 and two strains Rhodococcus KZ1 and KZ2). Microorganisms were cultured on a semi-synthetic medium to achieve maximum abundance, and the genes for the biodegradation of petroleum hydrocarbons were induced by additives at the end of fermentations. The microbial abundance at the end of cultivation with the addition of salicylate reached 7×109, with the addition of glucose – 1×109 CFU/ml, and with the addition of diesel fuel – 3.2×109 CFU/ml. Lyophilization at 35°C and a pressure of 4 μm Hg yielded a dry preparation with a microbial abundance of 8.0×1010 CFU/g. After storage for 6 months at 4-8°C, there was no loss of viability of microorganisms. Field tests conducted at the Akshabulak oil waste landfill of Company-Daulet Asia LLP showed the effectiveness of the control sample of the biopreparation. The degree of soil purification from petroleum products in 4 weeks was 70%, and in twelve weeks – 89.67%.